Optimization Of The Siman Application System As A Tool For State-Owned Asset Management At The Kantor Pelayanan Kekayaan Negara Dan Lelang Semarang - Cahaya, Rexajune Maharty Sukma; Elen Puspitasari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The management of State-Owned Goods (SOG) is a crucial aspect of asset management that requires an effective and efficient system. This study aims to analyze the optimization of the State Asset Management Information System (SIMAN) as a tool for managing SOG at the Office of State Treasury and Auction Service (KPKNL) Semarang. Using a descriptive qualitative approach, this research evaluates the implementation of SIMAN in improving the accuracy, efficiency, and transparency of SOG management. The findings indicate that the implementation of SIMAN successfully integrates all aspects of SOG management into a comprehensive digital platform, accelerating the processes of inventory, recording, and reporting SOG. Furthermore, the system facilitates monitoring and auditing by providing real-time and accurate data. The improvement in coordination among units and the use of user feedback are key factors in the system's optimization. However, challenges related to human resource training and technological infrastructure support still require further attention. Overall, SIMAN has had a positive impact on organizational performance and has strengthened accountability and transparency in the management of SOG at KPKNL Semarang.